Odgovornost za onečišćenje morskog okoliša: međunarodnopravna odgovornost država i građanskopravna odgovornost - Seršić, Maja; Pravni fakultet Sveučilišta u Zagrebu, Zagreb, Hrvatska (Faculty of Law of University of Zagreb, 2008)
U radu se razmatra međunarodnopravna odgovornost država za onečišćenje morskog okoliša. Ispituju se pretpostavke odgovornosti država za povredu međunarodne obveze i odgovornost bez protupravnosti. Ujedno se analiziraju osnovni međunarodni ugovori koji uređuju građanskopravnu odgovornost za štetu. States are responsible for the fulfilment of their international obligations concerning the protection and preservation of the marine environment, and they are liable in accordance with international law. As to the basis of responsibility, there are two possibilities: responsibility for wrongful conduct, and liability without wrongfulness (strict liability). As far as state responsibility for wrongful conduct is concerned, i.e., the violation of international obligations concerning the protection and preservation of the marine environment, there are, according to customary international law, two basic conditions for such responsibility: a breach of international obligation and the attributability to a state of some conduct constituting breach. These two elements are provided for in the draft articles on the Responsibility of States for Internationally Wrongful Acts, adopted in 2001 by the International Law Commission, which represents the codification and progressive development of international law in the field of state responsibility. It is possible that a state takes all the necessary measures to prevent pollution damage, but the damage nonetheless occurs. This may happen especially in connection with ultra-hazardous activities, such as the operation of large oil tankers or sea-bed drilling for oil and gas. In such cases, there is no wrongful conduct and no responsibility of states, since in customary international law there is no rule of strict liability of states. Such a basis for liability can be applied only if a treaty provides for it. In order to cover such situations where damage results from non-wrongful conduct of states, the International Law Commission started a study entitled “International Liability for Injurious Consequences Arising out of Acts not Prohibited by International Law”. A few topics on the agenda of the International Law Commission have proved to be controversial, and from the very beginning were met with strong scepticism and opposition in the legal doctrine. In dealing with this topic, the Commission has gone beyond the study of reparation of significant transboundary harm, to the management of a transboundary risk, with a strong emphasis on the prevention of transboundary losses. The integration of preventive and reparative elements in a single instrument led to the weakening of obligations that are twin pillars of the topic, viz the obligation of prevention and the obligation of compensation. According to the 1996 Draft articles, violation of the obligation of prevention entails no responsibility, and the obligation to compensate has become a negotiation duty. The 1997 session of the Commission opened the possibility for modifying these problematical solutions. The Working Group, established by the Commission to make recommendations on further work on the topic, noted that the scope and the content of the topic remained unclear due to, inter alia, some conceptual and theoretical difficulties. One of the basic recommendations of the Working Group was to treat separately the issues of prevention and international liability. The Commission accepted the suggested approach and in 2001 completed the first part of the task, i.e., the articles on the topic of prevention, and in 2006 the second, i.e., the principles on liability. The 2006 Draft principles on the allocation of loss in the case of transboundary harm arising out of hazardous activities did not bring anything new regarding this important issue. In fact, it can be said that these principles can be the basis for a regressive development of international law, recommending lower standards than those contained in the conventions dealing with civil liability for the damage caused by pollution. The states obviously do not want any rules that will make them liable in cases where there is no wrong. The non-existence of a general rule of strict liability of states and their hesitation to adopt a treaty containing provisions on such liability led to the eventual adoption of civil liability schemes where liability is directly channelled to private actors. The constantly increasing number of conventions devoted to civil liability for damage caused by pollution have some common features. They channel liability to the liable person, usually an operator, or, in the case of vessel-caused oil pollution, the shipowner. The liability is strict, usually with a few exonerating grounds, such as war, civil war, hostilities or natural phenomena amounting to vis major, the intention of a third party, the intention or negligence of a victim, and the negligence of those responsible for the navigation aid. The liable person is entitled to limit his/her liability to a certain amount, except in cases where he/she is personally at fault. The damage covered by the conventions comprises actual damage, the loss of income, the impairment of the environment and the costs of preventive measures. Compensation for the impairment of the environment is limited to the costs of the reasonable measures of reinstatement. In order to provide compensation even where no liability arises, or where the liable person is insolvent, additional compensation funds have been introduced. This was first done in relation to the 1969 Convention on Civil Liability for Oil Pollution Damage (CLC), which was supplemented by the 1971 Fund Convention. The role of the Fund is a subsidiary one: it has to provide additional compensation for pollution damage in cases where protection afforded by the 1969 CLC is inadequate. Consequently, it comes into operation when the shipowner is insolvent, when the total of the claims exceeds the limit of the shipowner's liability under the 1969 CLC, and when the shipowner is exonerated from liability under the 1969 CLC. Thus, the 1969 CLC and the 1971 Fund Convention provide basically for a two-tiered compensation system, with the shipowner being liable for the first tier of damages and the Fund for the second tier. Such a system is necessary in cases of extensive damage. In addition, the Fund functions at the first tier if the compensation cannot be obtained from the shipowner due to insolvency or exemption from liability. The FUND has no right of recourse against the shipowner for the compensation paid in accordance with the 1971 Fund Convention, i.e., when it functions at the second tier. The right of recourse exists only in cases where the FUND functions for the first tier because of the insolvency of the shipowner who is liable in accordance with the 1969 Convention. The Fund is financed by mandatory contributions from oil companies - oil importers in the Contracting States. The contribution amounts are assessed on the basis of the number of tons of oil annually received by sea at the ports and terminals of a Contracting State. The system of the 1969 Civil Liability Convention and the 1971 Fund Convention (which are in force as modified in 1992) transfer part of the economic burden to the oil industry. The Fund thus represents a collective guarantee of a group for individual liability. It acts as a guarantor when compensation, or full compensation, is not possible under the 1969 CLC, thus spreading major risk throughout the oil industry. Schemes similar to the 1971 Fund have been adopted, or are presently under discussion, for comparable risks. In this connection, mention should be made of the provisions of the 1996 International Convention on Liability and Compensation for Damage in Connection with the Carriage of Hazardous and Noxious Substances by Sea, the 1999 Protocol to the 1989 Basel Convention relating to liability and compensation for damage resulting from transboundary movements of hazardous waste and its disposal, and Annex VI on Environmental Liability to the 1991 Protocol on Environmental Protection to the Antarctic Treaty. Efforts are being made to elaborate the Liability Protocol to the Barcelona Convention for the Protection of the Mediterranean, and the rules on liability relating to the Protocol on Biosafety to the Biodiversity Convention.